Highly reproducible solid contact ion selective electrodes: emerging opportunities for potentiometry - a review - Cheong, Yi Heng (2022)
The solid contact ion-selective electrodes (SC-ISEs) have been extensively studied in the field of ion sensing as they offer the possibility of miniaturization, are relatively inexpensive in comparison to other analytical techniques and allow straightforward and routine analyses of ions in a number of clinical, environmental and industrial process samples. In recent years, significant interest has grown in the development of SC-ISEs with well-defined interfacialpotentials at the membrane, solid contact, and substrate electrode interfaces. This has resulted in interesting SC-ISEs exhibiting high electrode-to-electrode potential reproducibility, for those made in a single batch of electrodes, some approaching or exceeding those observed in liquid-contact ISEs. The advancement in the potential reproducibility of SC-ISEs has been partially achieved by scrutinizing insufficiently reproducible fabrication methods of SC-ISEs, or by introducing novel control measures or modifiers to components of the ISEs. This paper provides an overview of the methods as well as the challenges in establishing and maintaining reproducible potentials during the fabrication and use of novel SC-ISEs. The rules outlined in the works reviewed may form the basis of further development of cost-effective, user-friendly, limited calibration or calibration-free potentiometric SC-ISEs to achieve reliable ion analyses here and now.